Starting torque and torque ripple reduction using SVPWM based vector control of induction motor with nine-level cascaded multilevel inverter fed with solar PV power - Shashibhushan Shashibhushan; Savita Sonoli (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper is an attempt to develop an Induction Motor Drive System with Multilevel Inverter topology for reduced torque ripple application. A Nine level-cascaded multilevel inverter is developed for the induction motor drive with SVPWM control powered by boost converter fed using solar PV supply. The SVPWM control based implementation of vector control using a multilevel inverter topology needs a multilevel SVPWM control technique, which is implemented in this paper. The Solar power supplied is applied with the MPPT technique and the supplied DC power is fed to the three phase cascaded 9 level multilevel inverter. The vector control of induction motor is carried out using the SVPWM technique on the multilevel topology. The torque ripple reduction in the output is observed and compared with the vector control of induction motor. Matlab based implementation is carried out and the results are tabulated and inferred.